1995
DOI: 10.1128/jb.177.21.6049-6057.1995
|View full text |Cite
|
Sign up to set email alerts
|

The putative neuraminyllactose-binding hemagglutinin HpaA of Helicobacter pylori CCUG 17874 is a lipoprotein

Abstract: . 175:674-683, 1993), the gene for which has been cloned and sequenced. On the basis of the hydropathy plot of HpaA and the presence of a potential lipoprotein signal sequence and modification site, and because of the similarities of these features with those of the cell envelope lipoprotein Lpp20 of H. pylori, we examined the possibility that HpaA was also a lipoprotein. Posttranslational processing of the HpaA protein expressed by the cloned gene was sensitive to globomycin, an inhibitor of the lipoprotein-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
72
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 51 publications
5
72
1
Order By: Relevance
“…Originally, the subcellular localization of both proteins was determined by cell fractionation followed by sarcosyl solubilization of inner membrane proteins. HpaA was found to be cytoplasmic and inner membrane situated, whereas Lpp20 was isolated from both the inner and the outer membrane fractions of H. pylori cells [25,40]. Further systematic examination, conducted by different methods, contradicted previous results and revealed that HpaA is a flagellar sheath protein and Lpp 20 is an outer membrane antigen released from cells inside membrane vesicles [17,21].…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…Originally, the subcellular localization of both proteins was determined by cell fractionation followed by sarcosyl solubilization of inner membrane proteins. HpaA was found to be cytoplasmic and inner membrane situated, whereas Lpp20 was isolated from both the inner and the outer membrane fractions of H. pylori cells [25,40]. Further systematic examination, conducted by different methods, contradicted previous results and revealed that HpaA is a flagellar sheath protein and Lpp 20 is an outer membrane antigen released from cells inside membrane vesicles [17,21].…”
Section: Discussioncontrasting
confidence: 41%
“…All our attempts to confirm the lipoprotein nature of Tip-a by growing H. pylori cells in the presence of labeled palmitic acid were unsuccessful. Similar difficulties were encountered by Kostrzynska et al and O'Toole et al during their work on H. pylori Lpp20 and HpaA [25,40].…”
Section: Discussionmentioning
confidence: 69%
“…H. pylori possesses several putative colonization factors, including flagella motility (Marshall & Warren, 1984), various adhesins (Evans et al, 1993;Falk et al, 1993;O'Toole et al, 1995), vacA (Salama et al, 2001) and urease (Marshall & Warren, 1984;Tsuda et al, 1994), some of which have been shown to be necessary for gastric colonization. Isogenic flaA 2 , flaB 2 and flaA flaB 2 mutant strains do not show full motility, and are unable to form effective colonies in the stomachs of germ-free piglets (Eaton et al, 1996).…”
Section: Implications Of Experimental Datamentioning
confidence: 99%
“…The outer membrane proteins in Gram-negative bacteria have particular significance as a potential target for protective immunity [16]. Class 1 outer membrane protein (PorA) is a major component of the outer membrane of Neisseria meningitidis and functions as a cationic porin [17].…”
Section: Discussionmentioning
confidence: 99%